Mediation: A Viable Mechanism for Sustainable Development and Promoting Amicable Settlement of Litigated Disputes in Nigeria - Ayinla, Lukman A. (NIU Journal of Social Sciences, 2017)
The various problems associated with litigation like delay, enmity and acrimony prompted the desire for Alternative Dispute Resolution (ADR) mechanisms. Mediation is a certified mechanism that encourages peaceful resolution of dispute between parties and still preserves future harmonious relationship. Litigation defeats this purpose, thus mediation has the advantages of being a faster, cheaper and consensual process but the challenges lie in the lack of uniformity in practice, lack of adequate training and generally, lack of proper administration. The paper adopts the qualitative and quantitative methodology to address the challenges. It is shown that mediation deserves to be fully embedded in the system for sustainable development. It is found that the use of mediation in resolving dispute in Nigeria is faster, cheaper, consensual and removes acrimony between parties, taking a cue from the result of the pilot programmes in some states of the Federation. Key Words : ADR, Mediation, Traditional Mediation, Court-Annexed Mediation and Nigeria.